Comunicação e identidade: apropriação e estratégias do Movimento Xingu Vivo para Sempre em reação à Hidrelétrica de Belo Monte - FERREIRA, Jaqueline Almeida (Universidade Federal do Pará, 2014)
There is a trajectory of collective action in the Brazilian Amazon that has the quest for understanding and recognition of his speech to claim their livelihoods and rationality. This collective action, represented by the Xingu Alive Forever Movement (MXVPS, in portuguese), a coalition of organizations that embody the Belo Monte hydroelectric your ultimate symbol of opposition, seeks understanding and recognition of your speech through the appropriation of communication tools, particularly internet and its technological apparatus, and media culture (KELLNER, 200l), with all its icons of power and formatting of cultures and identities in contemporary times. The appropriation process undertaken by MXVPS does not happen fortuitously, but has a methodology, an action to recognize the "adversaries", appropriate them and make them, strategically, through the mediation of culture and identity, turn into something else, in other ways, now useful to counter-hegemonic struggle for recognition. The MXVPS engenders its action by: 1) the history of the groups that make up the collective, a history of human rights violations and silencing; 2) the representations and meanings of their identities, especially in the national and international stage, and 3) the perception of the political groups around for the results of action. This research findings point to the existence of a paradigmatic trajectory of communication in the Amazon in response to a major development project, with specific methodologies guided by discursive acts and identity. They are strategies that are intended, by means of Theory of Communicative Action (HABERMAS, 1987), aimed at mutual understanding, make valid claims and speeches, leading to recognition and, potentially, to meet their demands . This initiative was undertaken by means of communicative acts, still has the potential structuring of public space, the prospect of a fight (protagonist) to insert them (not as historically marginal group, but as a emancipated actor of their desires and intentions) in the contentious area of policy-making, focusing on social and political changes (and, potentially, normative) that affecting their territories, identities and modes of symbolic and material reproduction.